1996
DOI: 10.1086/647316
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Use in a University Medical Center: Comparison With Hospital Infection Control Practices Advisory Committee Guidelines

Abstract: Vancomycin use in our teaching center often was inconsistent with HICPAC guidelines. Information from the audit will be useful for designing strategies to improve vancomycin use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 10 publications
5
32
1
1
Order By: Relevance
“…In a Brazilian tertiary hospital, the empiric treatment was responsible for 81.1% of appropriate vancomycin use (because of hospital epidemiology) and 65.2% was inappropriate [36]. In other studies, the empiric treatment with vancomycin was considered the second largest category of inappropriate use (26%), and in others two studies it was considered the first, with 67% of inappropriate use [8,27,37].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a Brazilian tertiary hospital, the empiric treatment was responsible for 81.1% of appropriate vancomycin use (because of hospital epidemiology) and 65.2% was inappropriate [36]. In other studies, the empiric treatment with vancomycin was considered the second largest category of inappropriate use (26%), and in others two studies it was considered the first, with 67% of inappropriate use [8,27,37].…”
Section: Resultsmentioning
confidence: 98%
“…The empiric use in other studies [8,27,37] varied between 33% and 71%, among all patients that received vancomycin, Success rates in the management of Gram-positive infections (post surgical patients, ventilator-associated pneumonia, peritonitis, bacteremia and meningitis) were enhanced by early therapy with active agents against the organisms later identified by the appropriate culture. Inadequate therapy is closely correlated with adverse patient outcomes, including increased rates of hospital mortality [35,38,39].…”
Section: Discussionmentioning
confidence: 98%
“…Ninety-five patients (72.0%), among all patients, received empiric treatment of suspected Gram-positive infections. In previous studies, the reported empiric use varied between 33% and 71%, among all patients that received vancomycin [12,20,34]. Success rates in the management of Gram-positive infections (post surgical patients, ventilator-associated pneumonia, peritonitis, bacteremia …”
Section: Discussionmentioning
confidence: 99%
“…The empiric use was responsible for 75.4% of prescriptions considered adequate, because of hospital epidemiology ( Table 1). The empiric treatment with vancomycin was considered the second largest category of inappropriate use (26%), and in others two studies it was considered the first, with 67% of inappropriate use [12,20,34]. For instance, the HICPAC guidelines state that vancomycin is the appropriate treatment for infections caused by Grampositive microorganisms in patients who have serious allergies to beta-lactam antibiotics; we considered "appropriate" the unique case of allergy that was cited in patient's chart, though the allergy severity wasn't specified.…”
Section: Appropriate Use Criteriamentioning
confidence: 99%
See 1 more Smart Citation